Antibodies and cryptographic hash functions: quantifying the specificity paradox - Petrella, Robert J. (Frontiers in Immunology, 2025)
The specificity of the immune response is critical to its biological function, yet the generality of immune recognition implies that antibody binding is multispecific or degenerate. The current work explores and quantifies this paradox through a systems analysis approach that incorporates set theoretic ideas and an application of structural and statistical modeling to prior experimental immunological and biochemical data. Order-of-magnitude estimates are computed for the average degeneracies and specificities of antibodies and epitopes using a chemico-spatial model for epitope diversity and a binary model for antibody-antigen binding. The results illustrate and quantify how the humoral immune system achieves both high specificity and high degeneracy simultaneously by effectively decoupling the two properties, similarly to programs in cryptography called secure hash algorithms (SHAs), which display the same paradoxical features. In addition, an antibody-epitope interaction probability model is used to help show how newly formed antibodies may avoid cross-reactivity with self-antigens despite their high degree of multispecificity and how the requirement of polyclonal binding likely improves the overall specificity of the immune response. Because they describe the relationships between various statistical parameters in humoral immunity, the models developed here may also have predictive utility.